The Ecofisio Mobile App for Assessment and Diagnosis Using Ultrasound Imaging for Undergraduate Health Science Students: Multicenter Randomized Controlled Trial - Lozano-Lozano, Mario; Galiano-Castillo, Noelia; Fernández-Lao, Carolina; Postigo-Martin, Paula; Álvarez-Salvago, Francisco; Arroyo-Morales, Manuel; Cantarero-Villanueva, Irene (Journal of Medical Internet Research, 2020)
BackgroundGeneration Z is starting to reach college age. They have adopted technology from an early age and have a deep dependence on it; therefore, they have become more drawn to the virtual world. M-learning has experienced huge growth in recent years, both in the medical context and in medical and health sciences education. Ultrasound imaging is an important diagnosis technique in physiotherapy, especially in sports pathology. M-learning systems could be useful tools for improving the comprehension of ultrasound concepts and the acquisition of professional competencies. ObjectiveThe purpose of this study was to evaluate the efficacy and use of an interactive platform accessible through mobile devices—Ecofisio—using ultrasound imaging for the development of professional competencies in the evaluation and diagnosis of sports pathologies. MethodsParticipants included 110 undergraduate students who were placed into one of two groups of a randomized controlled multicenter study: control group (ie, traditional learning) and experimental group (ie, Ecofisio mobile app). Participants’ theoretical knowledge was assessed using a multiple-choice questionnaire (MCQ); students were also assessed by means of the Objective Structured Clinical Examination (OSCE). Moreover, a satisfaction survey was completed by the students. ResultsThe statistical analyses revealed that Ecofisio was effective in most of the processes evaluated when compared with the traditional learning method: all OSCE stations, P<.001; MCQ, 43 versus 15 students passed in the Ecofisio and control groups, respectively, P<.001. Moreover, the results revealed that the students found the app to be attractive and useful. ConclusionsThe Ecofisio mobile app may be an effective way for physiotherapy students to obtain adequate professional competencies regarding evaluation and diagnosis of sports pathologies. Trial RegistrationClinicalTrials.gov NCT04138511; https://clinicaltrials.gov/ct2/show/NCT04138511